Assessing multi-stakeholder approach in the relationship between ISO/TS16949 with organizational performance - Mousapour, Hojatallah (2014)
Business organizations need to have a proactive approach to fulfill stakeholder needs and interests. In line with stakeholder theory, ISO/TS16949 is a standard that has been developed to enhance organizational performance through fulfilling interested parties needs and interests. Based on literature reviewed, studies on the effect of the standard on organizational performance are few and far between. The study investigate the mediating effect of stakeholder relationship and satisfaction as well as moderating effect of firm size and industry type on the relationship between ISO/TS16949 implementation and organizational performance. A quantitative methodology using a cross-sectional survey method was used to investigate the relationship between variables. Data were collected from a stratified random sample of 272 automotive companies in Iran. The overall response rate was 76.1%. The relationships between variables were examined using structural equation modelling (SEM) technique and partial least squares (PLS) software was used. The indirect exploratory effect of the moderators was examined using multi-group analysis (MGA) method. The results revealed there is a significant positive relationship between ISO/TS16949 implementation, stakeholder relationship and stakeholder satisfaction. Besides that, the results disclosed that the implementation of ISO/TS16949 standard through the mediating variables of stakeholder relationship and stakeholder satisfaction has a positive effect on organizational performance. Furthermore, the results of multi-group analysis confirmed the relationship between ISO/TS16949 implementation, stakeholders’ relationship, stakeholders’ satisfaction and organizational performance is moderated by firm size and industry type. The study combined resource-based theory, resource dependence and stakeholder theories to develop a new theoretical framework to demonstrate the importance of social capital in improving organizational performance. Moreover, the study has provided a new platform to effectively implement ISO/TS16949.